OPTIMALITY CONDITIONS IN NONLINEAR VECTOR OPTIMIZATION WITH VARIABLE ORDERING STRUCTURES - Jahn, Johannes; Khan, Akhtar A. (Pure and Applied Functional Analysis, 2021)
This paper investigates nonlinear vector optimization problems with variable ordering structures used for the objectives and the constraints. For these problems new necessary and sufficient optimality conditions are presented without differentiability assumptions. This theory works with non-constant Lagrange multipliers, it does not need any constraint qualification, and the functions are not assumed to be convex. These optimality conditions are applied to so-called conditional vector optimization problems being characterized by constraints and/or objective functions, which are only valid under a certain condition.
CRIS-Team Scopus Importer:2024-12-16
Keywords: optimality conditions; variable ordering structures; Vector optimization